Structural organization of cetyltrimethylammonium sulfate in aqueous solution: the effect of Na2SO4 - Feitosa, E.; Brazolin, MRS; Naal, RMZG; Del Lama, MPFDD; Lopes, JR; Loh, W.; Vasilescu, M. (Elsevier B.V., 2006)
We used dynamic light scattering (DLS), a steady-state fluorescence, time resolved fluorescence quenching (TRFQ), tensiometry, conductimetry, and isothermal titration calorimetry (ITC) to investigate the self-assembly of the cationic surfactant cetyltrimethylammonium sulfate (CTAS) in aqueous solution, which has SO42- as divalent counterion. We obtained the critical micelled concentration (cmc), aggregation number (N-agg), area per monomer (a(0)), hydrodynamic radius (R-H), and degree of counterion dissociation (alpha) of CTAS micelles in the absence and presence of up to 1 M Na2SO4 and at temperatures of 25 and 40 degrees C. Between 0.01 and 0.3 M salt the hydrodynamic radius of CTAS micelle R-H approximate to 16 angstrom is roughly independent on Na2SO4 concentration; below and above this concentration range R-H increases steeply with the salt concentration, indicating micelle structure transition, from spherical to rod-like structures. R-H increases only slightly as temperature increases from 25 to 40 degrees C, and the cmc decreases initially very steeply with Na2SO4 concentration up to about 10 mM, and thereafter it is constant. The area per surfactant at the water/air interface, a(0), initially increases steeply with Na2SO4 concentration, and then decrases above ca. 10 mM. Conductimetry gives alpha = 0.18 for the degree of counterion dissociation, and N-agg obtained by fluorescence methods increases with surfactant concentration but it is roughly independent of up to 80 mM salt. The ITC data yield cmc of 0.22 mM in water, and the calculated enthalpy change of micelle formation, Delta H-mic = 3.8 kJ mol(-1), Gibbs free energy of micellization of surfactant molecules, Delta G(mic) = -38.0 kJ mol(-1) and entropy T Delta S-mic = 41.7 kJ mol(-1) indicate that the formation of CTAS micelles is entropy-driven. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cationic surfactant; micelle; aggregation number; surface tension; dynamic light scattering; steady-state fluorescence; time resolved fluorescence; conductimetry; tensiometry; isothermal titration calorimetry